2016
DOI: 10.2174/0929867323666160119094313
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in Cancer: Favourable or Unfavourable?

Abstract: Eosinophils are granulocytic leukocytes residing in blood and tissues in the lung, breast, gastrointestinal and reproductive systems. Eosinophilia is uncommon in healthy individuals, however, it is associated with allergies, helminth infections and some inflammatory states. Eosinophilia has also been observed in cancer, including colorectal, breast, ovarian, cervical, oral squamous, Hodgkin's lymphoma and prostate cancer. Whether an increase in eosinophils leading to a favourable or unfavourable prognosis stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
128
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(132 citation statements)
references
References 0 publications
2
128
1
1
Order By: Relevance
“…86-91), but by enhancing the infiltration of CD8 + T cells via secretion of chemoattractants and normalizing tumor vessels, thus providing a mechanistic link to understanding why an increased eosinophil count may herald a better outcome (92). Of note is that tumor eosinophil infiltration has been described as favorable (e.g., in colon cancer) (93) or unfavorable (94). Its occurrence and relevance in human melanoma remain to be studied in more detail, but it is striking that Soiffer et al observed both blood eosinophilia and degranulating eosinophils in regressing melanoma metastases upon vaccination with GM-CSF-secreting autologous melanoma cells (95).…”
Section: Discussionmentioning
confidence: 99%
“…86-91), but by enhancing the infiltration of CD8 + T cells via secretion of chemoattractants and normalizing tumor vessels, thus providing a mechanistic link to understanding why an increased eosinophil count may herald a better outcome (92). Of note is that tumor eosinophil infiltration has been described as favorable (e.g., in colon cancer) (93) or unfavorable (94). Its occurrence and relevance in human melanoma remain to be studied in more detail, but it is striking that Soiffer et al observed both blood eosinophilia and degranulating eosinophils in regressing melanoma metastases upon vaccination with GM-CSF-secreting autologous melanoma cells (95).…”
Section: Discussionmentioning
confidence: 99%
“…25 In this context, TATE has been widely studied, as previously revised. 4,6,[26][27][28][29][30][31] In this study, we aimed at reviewing the prognostic value of TATE in CRC. In contrast to previous reviews, which summarized this topic in the context of wider subjects, 4,6,26,28,29,31 our review included a larger number of studies and provided more detailed information on TATE characterization and on the association between TATE and other clinicopathological features in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…This role of macrophages in normal development also appears to be subverted by tumors of the mammary gland to promote the escape of the tumor cells from the local environment and enhance their rate of metastasis. These data emphasize the dual role of macrophages in the promotion of epithelial growth in normal and cancer states [15] Eosinophils are correlated to linked to a favourable prognosis in colorectal, breast and prostate cancers [16].…”
Section: Mini Reviewmentioning
confidence: 78%
“…In other studies, certain types of lymphoid and solid tumors have been associated with the infiltration of eosinophils into cancerous tissues [16][17][18], particularly specific lymphomas and Hodgkin's disease. Although tumor-related eosinophilia was considered to be an epiphenomenon arising from the spontaneous elaboration of IL-5 from tumor cells, or overproduction of T cells during chemotherapy with IL-2 [19], there is evidence of eosinophil activation as a result of IL-2 anticancer therapy [20,21].…”
Section: Mini Reviewmentioning
confidence: 99%